(untitled) (AYUSHDHARA, 2018)
Tinnitus is the sensation of hearing ringing, buzzing, hissing, chirping, whistling, or other sounds. The noise can be intermittent or continuous, and can vary in loudness. It is often worse when background noise is low. On analyzing the disease condition with Ayurvedic approach, it seems to be nearer to Vata Kapha dominant Karna Nada and needs to be treated at local as well as systemic level. Aim: To evaluate the effect of proposed Ayurvedic treatment protocol in the patients of tinnitus. Materials and Methods: The studies were conducted in 15 patients of Karna Nada and in all of them Nasya with Erandadi Taila and Karnapurana with Sarshapa Taila were given for 1 months. Results: It revealed statistically extremely significant relief in tinnitus. Furthermore, sustained relief was found in follow-up. Conclusion: Ayurvedic treatment protocol is effective in the management of tinnitus.